1997
DOI: 10.1037/0022-0663.89.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in first-grade mathematics strategy use: Social and metacognitive influences.

Abstract: Social and metacognitive contributors to gender differences in 1st grader's mathematics strategy use were explored. Fifty-eight children solved addition and subtraction problems individually and in groups of 3 in October, January, and May. The children's strategy use was assessed individually, as well as their metacognitive knowledge for mathematics strategies and their rationales for the use of different mathematics strategies. The children also solved addition and subtraction problems in groups. Gender diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
85
3
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 42 publications
22
85
3
3
Order By: Relevance
“…When solving multiplication problems, men more frequently used retrieval than did women, an effect observed earlier (see, e.g., Carr & Jessup, 1997;Carr et al, 1999;Fennema, Carpenter, Jacobs, Franke, & Levi, 1998;Geary et al, 2000). We also observed more efficient retrieval use in men than in women, which confirms the hypothesis that gender differences in mental arithmetic are due to the fact that retrieval use is faster in men than in women (Royer et al, 1999).…”
Section: The Impact Of Individual Differencessupporting
confidence: 88%
See 1 more Smart Citation
“…When solving multiplication problems, men more frequently used retrieval than did women, an effect observed earlier (see, e.g., Carr & Jessup, 1997;Carr et al, 1999;Fennema, Carpenter, Jacobs, Franke, & Levi, 1998;Geary et al, 2000). We also observed more efficient retrieval use in men than in women, which confirms the hypothesis that gender differences in mental arithmetic are due to the fact that retrieval use is faster in men than in women (Royer et al, 1999).…”
Section: The Impact Of Individual Differencessupporting
confidence: 88%
“…Gender effects have been investigated in children, rather than in adults. Several studies with children showed more frequent and more efficient retrieval use in boys than in girls (see, e.g., Carr & Jessup, 1997;Carr, Jessup, & Fuller, 1999;Royer, Tronsky, Chan, Jackson, & Marchant, 1999). Whether these differences exist in adulthood is a debated topic.…”
mentioning
confidence: 99%
“…In these studies, sex differences, favoring males, have been found for children's and young adults' strategic approaches to solving arithmetic problems and in the speed of executing some of the underlying component processes (Carr & Jessup, 1997;Carr et al, 1999;Fennema et al, 1998;Geary et al, 1993). The results are, however, inconsistent with Hyde et al's (1990) meta-analytic finding of no sex difference in computational abilities for 15-to 18-year-olds and a female advantage through early adolescence.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies of elementary-school children suggest no sex difference in overall arithmetical performance, but sex differences in problem-solving approaches are often found (Carr & Jessup, 1997;Carr, Jessup, & Fuller, 1999;Fennema, Carpenter, Jacobs, Franke, & Levi, 1998; but see Siegler, 1988). In these studies, boys used direct retrieval and covert strategies (e.g., mental counting) more often than girls did and girls used finger counting and overt strategies (e.g., blocks) more often than boys did.…”
mentioning
confidence: 73%
See 1 more Smart Citation